Beta-Band Functional Connectivity Influences Audiovisual Integration in Older Age: An EEG Study - Wang, Luyao; Wang, Wenhui; Yan, Tianyi; Song, Jiayong; Yang, Weiping; Wang, Bin; Go, Ritsu; Huang, Qiang; Wu, Jinglong (Frontiers in Aging Neuroscience, 2017)
Audiovisual integration occurs frequently and has been shown to exhibit age-related differences via behaviour experiments or time-frequency analyses. In the present study, we examined whether functional connectivity influences audiovisual integration during normal aging. Visual, auditory, and audiovisual stimuli were randomly presented peripherally; during this time, participants were asked to respond immediately to the target stimulus. Electroencephalography (EEG) recordings captured visual, auditory, and audiovisual processing in 12 old (60-78 years) and 12 young (22-28 years) male adults. For non-target stimuli, we focused on alpha (8-13 Hz), beta (13-30 Hz), and gamma (30-50 Hz) bands. We applied the Phase Lag Index (PLI) to study the dynamics of functional connectivity. Then, the network topology parameters, which included the clustering coefficient, path length, small-worldness global efficiency, local efficiency and degree, were calculated for each condition. For the target stimulus, a race model was used to analyse the response time. Then, a Pearson correlation was used to test the relationship between each network topology parameters and response time. The results showed that old adults activated stronger connections during audiovisual processing in the beta band. The relationship between network topology parameters and the performance of audiovisual integration was detected only in old adults. Thus, we concluded that old adults who have a higher load during audiovisual integration need more cognitive resources. Furthermore, increased beta band functional connectivity influences the performance of audiovisual integration during normal aging.